RETRACTED: Digitalization in construction: transformation of procedural approaches and project optimization in order to increase the profitability of the industry - Zatsarinnaya Elena; Barinov Sergey; Plekhanova Svetlana; Khonchev Mikhail (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001